Determining the causes of divorce in Perlis using fuzzy analytic hierarchy process / Mohd Fazril Izhar Mohd Idris, Khairu Azlan Abd Aziz and Muhammad Farhan Mohd Kamarulzaman - Mohd Idris, Mohd Fazril Izhar; Abd Aziz, Khairu Azlan; Mohd Kamarulzaman, Muhammad Farhan (Universiti Teknologi MARA, Perlis, 2019)
Divorce is one of the most common problems in the world and Malaysia is also considered as one of the countries that has many divorce cases. By definition, divorce is the legal dissolution of a marriage by a court or other competent body. Divorce is also categorized as an unfortunate occurrence as it would cause negative feelings and behaviors to someone who experienced it. Furthermore, there are nine factors of divorce used in the study which are infidelity, emotional problem, drugs problem, sexual problem, communication problem, problem with in-law, married too young and job conflict. Hence, the strongest factor needs to be determined as a precaution to people who want to married and people who are already married. Therefore, the best and suitable method to determine the strongest factor of divorces in Perlis is by using Fuzzy Analytic Hierarchy Process (FAHP). This is due to the capability and the ability of the FAHP in achieving better accuracy and consistency in the decision makers' judgment. The method was conducted by using questionnaires and interview sessions with six selected respondents from Perlis State Islamic Affairs and Malay Customs and Perlis Syariah Judiciary Department. After that, the respondents were asked to rate the pairwise comparisons by using Saaty Scale which is from one to nine. Then, all the surveys were collected and converted into triangular fuzzy number prior further analysis by using Microsoft Excel. The analysis shows that the strongest factor of divorces in Perlis is drugs problem with the normalized relative weight of 0.203. Hence, Perlis residents need to be aware of the factors of divorce in the state and they can try to reduce the number of divorce cases in Perlis as well.